Meningkatkan Pemahaman Sadar Gizi dan Pencegahan Stunting Sejak Dini Siswa SDN Gilii Timur 2 Kecamatan Kamal Bangkalan - imamromadlani; Lailatul Muarofah Hanim; Imam Sofyan; Nur Wanda Ramadani; Abd Wafi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This community service program aims to increase the elementary school students' understanding of nutrition and health, especially in terms of stunting in Gili Timur Village. The society needs to encourage their awareness of the importance of balanced nutrition. Stunting is a chronic nutritional problem affecting children's physical and cognitive growth, which can be prevented with early education. The socialization program carried out by KKN-Tematic students involved 4th and 5th grade students in elementary school with an interactive approach, interesting learning media, and participatory discussions. The results of this program showed a significant increase in students' understanding of the causes, impacts, and prevention of stunting. In addition, students gained insight into the importance of a balanced health upon the food and drink consumed. It is expected that this program contributes to efforts to reduce stunting rates and improve the quality of health of future generations.